2014
DOI: 10.1007/978-3-319-05161-1_6
|View full text |Cite
|
Sign up to set email alerts
|

TRPs and Pain

Abstract: Pain usually occurs as a result of tissue damage and has a role in healing and protection. However, in certain conditions it has no functional purpose and can become chronic and debilitating. A demand for more effective treatments to deal with this highly prevalent problem requires a better understanding of the underlying mechanisms. TRP channels are associated with numerous sensory functions across a wide range of species. Investigation into the expression patterns, electrophysiological properties and the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 144 publications
(179 reference statements)
0
16
0
Order By: Relevance
“…The present study corroborates the fact that modification of OA in C 3 and C 28 positions results in enhancement of biological properties. Furthermore, all oleanane-derived compounds also display superior analgesic activity in formalin-induced pain [ 23 ]. The formalin test is a useful nociceptive model in that pain is spontaneous and responses are observed in freely moving animals.…”
Section: Discussionmentioning
confidence: 99%
“…The present study corroborates the fact that modification of OA in C 3 and C 28 positions results in enhancement of biological properties. Furthermore, all oleanane-derived compounds also display superior analgesic activity in formalin-induced pain [ 23 ]. The formalin test is a useful nociceptive model in that pain is spontaneous and responses are observed in freely moving animals.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the inciting event (inflammation, nerve injury), not only peripheral but also spinal and/or supraspinal signaling pathways can all conspire to amplify and produce persistence of pain [46]. At the level of the nociceptor, the basis of acute inflammatory pain and its persistence has been studied with a focus on inflammation-induced modifications of ion channel function that result in lowering activation thresholds in the presence of the ongoing production of endogenous sensitizing molecules [3, 7, 8]. However, other processes that drive the persistence and transition from acute to chronic pain continue to be examined [5, 912].…”
Section: Introductionmentioning
confidence: 99%
“…In studies conducted using human tissue, TRPV1 and TRPV3 levels were found to be decreased in the skin of patients with diabetic or other painful neuropathies but increased in intact nerve fibers in certain patients with pain hypersensitivity, whereas the level of TRPV4 was observed to remain unchanged [99,155]. One potential mechanism has been suggested for these phenotypic changes: the damaged neurons might release growth factors and neurotransmitters into the surrounding area and, consequently, cause an increase in the excitability of surrounding neurons [13, 153,156,157]. These dynamic changes contrast the changes detected in inflammation, in which TRP channels are generally upregulated (see above); this reflects the notion that inflammatory pain simply features a Bsurplus^of nociceptive signaling, whereas the sensory abnormalities of neuropathies include not only hypersensitivity (hyperalgesia or allodynia), but also paresthesias, hypoesthesia, or complete deficits perceived as numbness [158] (Fig.…”
Section: Trps In Neuropathic Painmentioning
confidence: 98%